Evaluation Of The Village Fund Program In Kadolomoko Village, Kokalukuna District, Baubau City - Edo, Hasrianti; Basir, Muh Askal; Nastia, Nastia (Jurnal Ilmu Sosial Mamangan, 2024)
Inadequate human resources are one of the factors that hinder the maximum development program based on this problem, this study aims to find out how the Management of Village Funds in the context of improving facilities and infrastructure and community empowerment in Kadolomoko Village, Kokalukan District, Baubau City. This research is designed as a qualitative research with the intention of excavating or building a procession or explaining the meaning behind reality. The results of the study showed that the evaluation of the Village fund program in Kadolomoko Village from the indicators of effectiveness, efficiency, adequacy, responsiveness, and accuracy of the results stated that they were quite good while from the leveling indicators the results stated that they were not good, this was due to the lack of transparency in the allocation and management of village funds so that the development of facilities and infrastructure and community empowerment were uneven.